Russian Ideational Roots of Jewish Thought and Hebrew Literature - Lapidus, Rina (Academic Studies Press, 2024)
This book demonstrates how the Russian thought and literature of the eighteenth and nineteenth centuries influenced Jewish thought and Hebrew literature. Through a comparative analysis of an extensive corpus of writings by renowned Russian and Jewish thinkers, the book reveals how ideas regarding the need for a national awakening penetrated from Russian to Jewish thought. The Jewish thinkers who embraced these notions adapted them to the reality and experience of Jewish life in Central and Eastern Europe. Likewise, portrayals of an individual’s quest for the authentic and just God in Russian literary works gained purchase in ideological Hebrew literature, where the hero searches for a true path to achieve spiritual, social, and national well-being for the Jewish people. Absorption of ideological influences is a universal phenomenon that is instrumental to progress and cultural development, and it is accepted in Jewish culture as well.